EFFECTS OF TREATMENT OF CHILDREN WITH MODERATE AND SEVERE INTELLECTUAL DISABILITY IN DAY CARE CENTERS (Annual of the Faculty of Philosophy in Skopje, 2014)
Process of non-institutionalization withdraws series of changes in the system of social protection in Republic of Macedonia. Institutional protection is replaced by non-institutionalization forms ofprotection thus children with special educational needs are placed within their biological families or fosters families and in the same time they are included with treatment in day care centers.These day centers are functioning as centers for treatment of children with moderate and severe intellectual disabilities and also provide support to families so they can easily complete their work and family obligations. With their activities pointed to its end users, users families but also the community where they ’re operating, these day care centers contributes for easy socialization, adaptation, initiating the independence, improvement of social literacy, as well as motility correction, speech and development of cognitive functions of children covered with treatment in these day care centers.The research is conducted with objective to evaluate the satisfaction of parents of children with moderate and severe intellectual disability-users of day> care centers services for children with moderate and severe intellectual disability in Skopje, Kumanovo and Veles based on evaluation of the metrics stated above.
Keywords: CHILDREN WITH MODERATE AND SEVERE INTELLECTUAL DISABILITY; NON-INSTITUTIONAL PROTECTION; DAY CARE CENTERS; TREATMENT EFFECTS